Hubungan Volume Prostat dengan Derajat International Prostate Symptoms Score (IPSS) pada Pasien Pembesaran Prostat Jinak di Desa Meliling, Kecamatan Kerambitan, Kabupaten Tabanan Tahun 2024 - Suastari, Ni Made Putri; Mahayani, Ni Made Widya; Dinata, Dewa Komang Agung Hersya Paritranaya (Dinasti Research, 2025)
Benign prostate enlargement is one of the most common urological diseases found in the elderly population whose incidence increases with age. The method used in this study was observational analytic with a cross-sectional research design. This study was conducted in Banjar Jagatamu, Meliling Village, Kerambitan District, Tabanan Regency in November 2024 with a sample of 71 people who met the established criteria. Using transabdominal ultrasound examination to assess prostate volume by one radiologist and IPSS questionnaire containing 7 questions regarding lower urinary tract complaints filled by respondents. The results of this study showed that based on prostate volume grade, most patients were found to be grade II, namely 40 patients (56.3%), while based on LUTS complaints assessed using IPSS, most patients had moderate symptoms, namely in 41 patients (57.7%). Based on the correlation test between prostate volume grade and IPSS degree, it was found that the relationship was 0.978, indicating a very strong relationship between the two variables. This indicates that the greater the prostate volume grading has a very strong relationship with the increasing degree of IPSS which is proven statistically significant (p<0.000).